Bola na rede: uma análise das estratégias comunicacionais de empresas esportivas no ambiente digital conectado - EHRENBERG, KARLA CALDAS (2016)
The use of social media as a means of promoting products, services and organizational content has grown in the last decades and has obtained especial attention in organizational communication planning and academic studies about the subject. Accordingly, the sports companies segment operates with importance, arousing interest and costumer empathy. Through bibliographic review and empirical study, this research It is intended to investigate the marketing communication actions of sports segment on the connected digital environment, through a multiple case study of Nike and Adidas companies. To collect the data, interviews were performed in depth with market professionals and applied a digital social networks research protocol on the companies studied profile. After collecting the data, these data were analyzed based on the theories studied in the initials chapters (which covered topics like organizational communication, digital communication, sport and sports communication), and it was possible to conclude, among other issues, that in the sports segment universe, the connected digital communication doesn’t prioritize the dialogue with its stakeholders, being essentially based on the unilateral spreading of content, nor exploit the potential of each available digital platforms, replicating content in different environments. Also, It was evident the use of the sports universe elements as strategic arguments of corporate communication, due to capacity to strengthen the relational ties with stakeholders through their symbolic appeals of easy social identification.